2014
DOI: 10.1371/journal.pone.0103407
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Methyl Jasmonate Treatment Increases Glucosinolate Biosynthesis and Quinone Reductase Activity in Kale Leaf Tissue

Abstract: Methyl jasmonate (MeJA) spray treatments were applied to the kale varieties ‘Dwarf Blue Curled Vates’ and ‘Red Winter’ in replicated field plantings in 2010 and 2011 to investigate alteration of glucosinolate (GS) composition in harvested leaf tissue. Aqueous solutions of 250 µM MeJA were sprayed to saturation on aerial plant tissues four days prior to harvest at commercial maturity. The MeJA treatment significantly increased gluconasturtiin (56%), glucobrassicin (98%), and neoglucobrassicin (150%) concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 43 publications
5
50
0
Order By: Relevance
“…Findings by Ku et al (2014) support our results of MeJA increasing endogenous JA under OT. Ku et al (2014) applied exogenous JA to kale plants grown consecutively for two years under open field conditions.…”
Section: Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…Findings by Ku et al (2014) support our results of MeJA increasing endogenous JA under OT. Ku et al (2014) applied exogenous JA to kale plants grown consecutively for two years under open field conditions.…”
Section: Tablesupporting
confidence: 88%
“…Findings by Ku et al (2014) support our results of MeJA increasing endogenous JA under OT. Ku et al (2014) applied exogenous JA to kale plants grown consecutively for two years under open field conditions. In the first year, when the plants experienced normal environmental conditions and little stress, they accumulated more endogenous JA in kale apical leaves.…”
Section: Tablesupporting
confidence: 88%
“…4 . This result agree with Gharechahi et al 29 in which MeJA, increase the C18:2 content in hairy root cultures of Silybum marianum L. Furthermore it has been found that JA or MeJA exogenously can induce the biosynthesis of JA endogenously 30 .…”
Section: Phenolic Compounds and Antioxidant Capacity In Callussupporting
confidence: 92%
“…Glucosinolate composition in kale and collard has been reported [9,12], but glucosinolate composition in different collard cultivars is still relatively less reported. Additionally, glucosinolate composition can be affected by various biotic and abiotic factors, complicating comparison of the result of different studies.…”
Section: Glucosinolatesmentioning
confidence: 99%
“…The healthpromoting effects of glucosinolates are in fact from their hydrolysis products, and anticarcinogenic activities of such hydrolysis products have been reported in cell culture, preclinical, and clinical studies [3,6,7]. The profile of glucosinolates of kale has been shown to vary depending on crop, cultivar, maturity, or plant tissue [8,9]. However, the glucosinolate profile in collard has only been reported relatively recently and there is a large variation in glucosinolate content, partially due to different cultivars investigated [10][11][12].…”
Section: Introductionmentioning
confidence: 99%